Firm fundamentals and sectoral heterogeneity in Sharia-compliant stock return volatility: Evidence from Indonesia‎ - Fithriyana, Rinda; Irfan, Andi; Sudirman, Wahyu Febri Ramadhan (Universitas Islam Indonesia, 2025)
IntroductionThe volatility of stock returns in Islamic equity markets is a critical concern for both investors and policymakers. Islamic screening principles restrict excessive leverage and speculative activities, potentially shaping volatility in distinct ways compared to conventional markets. Understanding how firm fundamentals affect volatility within the Indonesia Sharia Stock Index is essential for evaluating the stability and competitiveness of Islamic capital markets.ObjectivesThis study aims to examine whether firm fundamentals, i.e. profitability, liquidity, leverage, size, growth, and asset turnover, systematically influence stock return volatility in Sharia‐compliant firms. It also seeks to identify cross‐sector heterogeneity in these relationships, highlighting whether specific industries are more sensitive to fundamental determinants of volatility.MethodThe research employs a quantitative design using a panel of 200 nonfinancial firms listed in the Indonesia Sharia Stock Index over the 2019–2023 period. Approximately 4,000 firm–quarter observations were analyzed. Volatility was modeled through panel generalized autoregressive conditional heteroskedasticity estimation, while Chow, Wald, and likelihood ratio tests were applied to assess sectoral heterogeneity. The study incorporated firm fundamentals as independent variables with sector‐specific models to capture industry differences.ResultsThe findings reveal that profitability and liquidity significantly reduce stock return volatility, while leverage consistently increases it. Firm size emerges as the most powerful stabilizer, growth contributes to higher volatility, and asset turnover lowers volatility. The magnitude of these effects varies across industries: Energy and Basic Materials show the strongest sensitivity to fundamental shocks, while Utilities and Healthcare display weaker responses. Statistical tests confirm substantial cross‐sector heterogeneity in the relationship between fundamentals and volatility.ImplicationsThe results demonstrate that Islamic screening principles, particularly restrictions on leverage, effectively mitigate excessive risk in Sharia markets. The study reinforces the relevance of Modern Portfolio Theory and Arbitrage Pricing Theory in Islamic settings while emphasizing the need for sector‐sensitive investment strategies. Portfolio managers and regulators may use these insights to refine risk management practices and enhance the resilience of Islamic equity markets.Originality/NoveltyThis study offers a novel application of panel GARCH modeling to explore cross‐sectoral heterogeneity in an Islamic equity universe. It contributes empirical evidence that firm fundamentals significantly and differentially shape volatility across industries, thereby advancing both Islamic finance scholarship and practical portfolio construction in Sharia‐compliant markets.